Income inequality and technological progress: The effect of R&D incentives, integration, and spillovers. (13th August 2020) - Osório, António; Pinto, Alberto
Abstract: Recent years witnessed an increase in income inequality. Several explanations have been put forward. In the present paper, we consider a series of technologically related events that have been crucial for the increased income inequality, that is, public R&D incentives, increasing horizontal integration and spillover effects. We found that public R&D incentives and the increasing horizontal integration have biased the income distribution towards the top income group. In particular, the high‐skilled workers involved in the R&D process have benefited enormously from this process. Similarly, capital owners have seen an increase in their profits, because of the reduction in product market competition and technological improvements in the production process. We found the effect of knowledge spillovers to be less clear‐cut. We conclude discussing the implications of our results and suggesting possible solutions to the increasing income inequality. We call for the creation of supranational institutions, and for stricter legislation on competition and antitrust policy.